Challenges of implementing child-friendly school model in Surakarta, Indonesia - Siany Indria Liestyasari; Ravik Karsidi; Asrowi Asrowi; Abdul Rahman (Institute of Advanced Engineering and Science, 2023)
Indonesia adopted the UNICEF’s child-friendly school (CFS) model as the attempt protection and fulfillment of children’s rights in education. The top-down implementation of child-friendly schools and bureaucratic imperatives have made many schools not ready to implement the model so the child-friendly school program is still far from expectations and reality. Many interests in the implementation of child-friendly schools make students vulnerable to being the victims of education political policies. This article aims to explain school challenges in child-friendly school implementation. Qualitative method with case study approach used through observations, interviews, and focus group discussions at three senior high schools in Surakarta City, Indonesia. The results show that the challenges of implementing child-friendly schools lead to three things, namely mentoring and sustainability, technical implementation, and evaluation mechanism. The simultaneous CFS declarations have not been adapted to the readiness, willingness, and needs of each school. Fulfilling the challenges of implementation is able to make CFS not just a slogan but a school’s need to provide protection and fulfillment of children’s rights.